Sucessão da entomofauna associada a carcaças de Sus scrofa L. no sul do Brasil - Ries, Ana Carolina Reimann (2013)
Forensic entomology is the science applied in the use of insects allied to legal procedures, being used as a complementary tool for scientific police and crime scene investigators of the country in the determination of the post mortem interval (PMI). To this end, we mention two ways to determine the PMI: the age of immature specimens collected in association with carcasses and the following succession of insects present. In Brazil, few studies focus on forensic entomology, and data collected in a geographic area cannot be applied in other one due to the high diversity of insect species in the Country. Therefore, this study aimed to determine the pattern of entomofauna succession of decomposing carcasses in southern Brazil, correlating to the stages of decomposition and abiotic factors and evaluate the interference of larvae of Chrysomya albiceps in the detection of other species of scavengers insect larvae. The experiment was conducted at the Águas Belas Research Station and Production of the State Foundation for Agricultural Research in Viamão, in southern Brazil. It was used three domestic pigs with approximately 16 kg, slaughtered by firearm shooting and immediately placed in protection boxes with metal mesh. For the entomofauna sampling, it was used insect nets, manual collection and pitfall traps, collections being made daily at noon. The carcasses were observed and photographed, and the data of temperature and humidity were recorded. We captured 569 adult specimens, belonging to 29 families, 55 genera and 68 morphospecies. Scarabaeidae was the most abundant family among the adult insects, representing approximately 25% of the individuals collected, followed by Calliphoridae (23%). The 269 immature specimens sampled, comprising a genus and two species. The prevalence of Chrysomya albiceps was evident, with 97.4% of the individuals collected. It was observed five stages of decomposition during the fourteen days that comprised the experiment. The stage of decomposition with the largest number of individuals, adults and immatures, and species richness was black putrefaction, while in the skeletonization stage there was a large decrease of this number. The prevalence of immature C. albiceps during the decomposition process affected the detection of individuals of other scavenger species. Furthermore, only third instar specimens were collected, which may be related to predatory and cannibalistic behavior of the species over others.